Synthesizing ordered mesoporous Ni spheres with uniform and adjustable size through a one-step Pd2+-assisted soft-templating strategy. Issue 25 (20th June 2022) - Dong, Jing; Mi, Xueqin; Sun, Tingting; Zhang, Yixin; Jiang, Wenqian; Li, Fulin; Chen, Jianfeng; Xu, Lianbin
Abstract : This work presents a facile one-step Pd 2+ -assisted soft-templating strategy to prepare a series of ordered mesoporous Ni spheres (OMNiS) with highly uniform and tunable diameters. Abstract : Developing an effective way to synthesize uniform ordered mesoporous metal spheres with controllable diameter is important for enhancing their performance in various applications but remains a challenge. Herein, a one-step and facile Pd 2+ -assisted soft-templating strategy is reported to synthesize ordered mesoporous Ni spheres (OMNiS) with highly uniform and tunable diameters. In this synthesis methodology, lyotropic liquid crystals (LLCs) are used as a meso-structural template and Pd nuclei obtained from the reduction of Pd 2+ ions are used as nucleation sites for directing Ni deposition. The OMNiS samples with average sphere diameter ranging from 50 nm to 190 nm are produced by varying the amount of Pd 2+ in the LLC precursor, revealing that the Pd nuclei play a key role in improving the uniformity of the mesoporous Ni spheres and adjusting the sphere diameter. The satisfactory combination of uniform sphere size, high surface area, great conductivity, and highly ordered mesoporous structure for the optimal OMNiS-100 sample contributes to its superior electrocatalytic activity for the oxygen evolution reaction (OER) in an alkaline electrolyte with a low overpotential of 271 mV to drive a current density of 10 mA cm −2, which is much smaller than that of RuO2 (368 mV), along with a remarkable durability.